KAJIAN SOSIOLOGI AGAMA DALAM TEOLOGI: KERANGKA INTERDISIPLINER UNTUK MEMBACA IMAN, GEREJA, DAN MASYARAKAT - Imanuel Pangaibali (Diegesis : Jurnal Teologi, 2024)
This article examines the place of sociology of religion within theological reflection. It argues that theology cannot speak responsibly about church, mission, spirituality, and public witness without attending to the social locations, symbolic systems, power relations, and everyday practices through which religion is lived. Sociology of religion does not replace theology's normative claims about God, revelation, and salvation; rather, it clarifies the social conditions under which such claims are received, institutionalized, contested, and embodied. Using a qualitative literature-study method and interdisciplinary theological analysis, this study engages classical and contemporary theories from Durkheim, Weber, Berger, Bourdieu, Geertz, Casanova, Davie, McGuire, Taylor, and practical theologians such as Schreiter, Bevans, Tanner, Swinton, Mowat, Osmer, Graham, Bosch, and Volf. The findings show that sociology of religion offers at least five contributions to theology: it exposes the social construction of religious meaning; it helps theology discern the relation between faith, institution, and power; it sharpens contextual and public theology; it corrects abstract ecclesiology by attending to lived religion; and it strengthens pastoral, missional, and educational practices. The article concludes that an integrative model is needed: sociology describes how religion functions in society, while theology evaluates those functions in light of Scripture, tradition, and the vocation of the church.